Differentiating relationships in the workplace: A cultural perspective - Halim, Haslina; Abu Bakar, Hassan; Mohamad, Bahtiar (2016)
This study aimed to examine the constructs that constitute relationship differentiation in leader-member exchange relationships, which would provide unique theoretical insights and pragmatic applications for communication in the Malaysian workplace.Six-hundred questionnaires were distributed to employees of government, semi-government, and private organizations (n = 479).Results revealed that leader conceptual skills, communication openness, and trust contributed towards organizational citizenship behavior.Cultural considerations were invoked to explain certain findings of this study.